2007
DOI: 10.1002/cbdv.200790244
|View full text |Cite
|
Sign up to set email alerts
|

Two New Alkaloids from Brachystemma calycinum and Their Inhibitory Effects on Lymphocyte Proliferation

Abstract: Two new alkaloids, brachystemidines F (1) and G (2), were isolated from the roots of Brachystemma calycinum. Their structures were established on the basis of detailed spectroscopic analyses, including extensive NMR and HR-MS techniques. Compound 2, which exhibits an unusual N-hydroxydiazenyl (HO-N=N) moiety, is a potent immunosuppressive agent, as demonstrated by inhibition of mouse T- and B-lymphocyte proliferation, with IC50 values of 6.33 and 5.60 microg/ml, resp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Alkaloid brachystemidine G ( 99 ) was isolated from the roots of Brachystemma calycinum . This compound is a potent immunosuppressive agent, as demonstrated by its inhibition of mouse T and B-lymphocyte proliferation, with IC 50 value of 5.6 μg/mL [ 114 ]. The 1,2,4-triazine derivative ( 100 ) was extracted from the seeds of the tropical flowering plant Butea monosperma [ 115 ].…”
Section: Azo Metabolites Derived From Terrestrial and Marine Sourcesmentioning
confidence: 99%
“…Alkaloid brachystemidine G ( 99 ) was isolated from the roots of Brachystemma calycinum . This compound is a potent immunosuppressive agent, as demonstrated by its inhibition of mouse T and B-lymphocyte proliferation, with IC 50 value of 5.6 μg/mL [ 114 ]. The 1,2,4-triazine derivative ( 100 ) was extracted from the seeds of the tropical flowering plant Butea monosperma [ 115 ].…”
Section: Azo Metabolites Derived From Terrestrial and Marine Sourcesmentioning
confidence: 99%
“…Brachystemidine G ( 41 ) was isolated in 2007 from the roots of Brachystemma calycinum , a plant with widespread use in traditional medicine . Brachystemidine G ( 41 ) is essentially a nitrosoamide but exists as its N -hydroxydiazenyl tautomer.…”
Section: Natural Products Containing An N–n Bondmentioning
confidence: 99%
“…Brachystemidine G ( 41 ) is essentially a nitrosoamide but exists as its N -hydroxydiazenyl tautomer. The configuration of 41 could not be elucidated due to insufficient material . Brachystemidine G inhibited the proliferation of B- and T-lymphocytes from Balb/c mice …”
Section: Natural Products Containing An N–n Bondmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a Chinese folk medicine used to treat rheumatoid arthritis, limb numbness, impotence, and gonorrhea . Previous studies showed that it contains alkaloids and cyclic peptides. An extract of the whole plant was recently found to be able to reduce disease symptoms and the development of cartilagenous lesions in experimental dog osteoarthritis by inhibiting protease-activated receptor 2 . Inflammatory and immune processes are implicated in rheumatism, and it may be possible to isolate anti-inflammatory or immunoregulatory compounds from B. calycinum that may be useful in the treatment of DN.…”
mentioning
confidence: 99%